Distribution of annionic sites in glomerular basement membranes: their possible role in filtration and attachment. - Caulfield, J P (1976)
Lysozyme (pI = II) has been used to identify anionic sites in the glomerular capillary wall. A solution of 1-3% lysozyme was perfused into the left kidney at varying rates. After perfusion, the kidney was fixed in situ and processed for electron microscopy. Lysozyme was seen as an electron-dense deposit which was not present when succinylated lysozyme (pI = 4.5) or myoglobin (pI = 6.9) was perfused instead of native lysozyme. First, the epithelial cell plasma membrane was outlined by a 300-400 A electron-dense layer. Second, there were discrete dense deposits in the subepithelial portions (lamina rara externa) of the basement membrane which, in normal sections, extended from the epithelial cell membrane to the lamina densa and, in grazing section, formed a continuous reticular pattern.